Pengaruh Waktu Pemberian Probiotik Yang Berbeda Terhadap Respon Imun NonSpesifik Ikan Mas (Cyprinus Carpio L.) Yang Diuji Tantang Dengan Bakteri Aeromonas Salmonicida - Septiarini -; Esti Harpeni; Wardiyanto - (University of Lampung, 2012)
Common carp (Cyprinus carpio) is one of the consumption fish which has high economic value. However, the efforts to increase carp production obstracted by diseases such as furunculosis by A. salmonicida. So that we have to consider the disease prevention method which safer such as probiotic. The aims of this research were to know effect of the time administrations of probiotic on non-specific immune responses and to know the best time administration of probiotic on non-specific immune responses of common carp injected by A. salmonicida. The research was conducted from August to October 2011. The research used three treatments (without administration of probiotic, administration of probiotic once every day, and administration of probiotic once every five days) with four replications. Data of total leukocyte and percentage of differential leukocyte were analyzed by using ANOVA, while RPS and water qualities were analyzed descriptively. The results showed the time administrations of probiotic showed a real impact on improving non-specific immune responses characterized by increased total leukocyte in carp, administration of probiotic once every five days resulted better non-specific immune responses, which had been seen from the highest total leukocyte and the highest RPS after being injected by A. salmonicida.